Optimization of the process of special training of highly qualified biathletes taking into account the specifics of their competitive activities - Inakov, B. (Mental Enlightenment Scientific-Methodological Journal, 2025)
This study proposed and experimentally tested a methodology for improving the special training of biathletes, taking into account the peculiarities of competitive activity. The results of a pedagogical experiment conducted as part of the work are also presented. The main focus was on the development of combined training actions aimed at improving shooting accuracy and enhancing athletes' physical conditioning. The results of the experiment showed a significant improvement in the level of technical and tactical preparedness in the experimental group, which confirms the effectiveness of the proposed methodology.